(untitled) (Anwer Khan Modern Medical College Journal, 2017)
Osteoid ostemoa is benign bone tumor and third most common benign neoplasm of bone. Young male are frequently affected three times more than females. It can occur in any bone but most common in long bone such as femer and tibia. In routine ENT practice osteoma are infrequently found in temporal bones most commonly seen in external ear canal. Osteoid ostemoa in mastoid are rare. We present such a rare presentation of ostema arising form the left mastoid in a young female. Anwer Khan Modern Medical College Journal Vol. 8, No. 1: Jan 2017, P 71-72